Acid pretreatment increased lipid biomarker extractability: a case study to reveal soil organic matter input from rubber trees after long‐term cultivation. (27th November 2017) - Li, F. F.; Zhang, P. C.; Wu, D. P.; Xu, Y.; Chen, F. Y.; Chang, Z. F.; Chu, G.; Wang, L.; Pan, B.; Xing, B. S.
Abstract : The lipids extractable by organic solvents are important components of soil organic matter (SOM) and were used to trace the sources and degradation of SOM. Previous studies have suggested soil mineral protection of lipids, which might decrease the efficiency of extraction of some lipid compounds by organic solvents. Therefore, in this study we applied a mild acid treatment to remove most of the reactive mineral particles without altering SOM chemical structures. The SOM information provided by lipid biomarkers was different before and after acid treatment in this research. Because of the various chemical contents of lipids, the presence of reactive minerals might alter lipid biomarker signals considerably and could lead to the wrong conclusions. Based on lipid biomarker information obtained through acid‐aided extraction, we identified that the source for alkanoic acids was different from that for alkanols and alkanes. Alkanoic acids were derived from both original vegetation (bamboos) and new inputs from fresh rubber tree tissues, whereas alkanols and alkanes were mainly from the original vegetation. Various biomarker indices indicated an extended degradation of lipids after intensive rubber tree cultivation. The leaching of short‐chain aliphatic lipids and the new input of alkanoic acids in the surface soil were also considered to avoid the incorrect orientation of biomarker information. This study suggested that although the new input from rubber trees was evident in cultivated soil, cultivation activities might enhance the degradation of SOM and accelerate its turnover. The cycling of SOM thus needs to be investigated carefully to protect the ecosystems affected by intense human activity. Highlights: The extractability of lipids is enhanced after removal of reactive minerals. Various biomarkers indicate enhanced lipid degradation after cultivation. New input of SOM from rubber trees is suggested by alkanoic acid biomarkers. Cultivation activities accelerate SOM degradation and turnover.